Free-living nematodes of Mediterranean ports: A mandatory contribution for their use in ecological quality assessment. (July 2022) - Franzo, Annalisa; Baldrighi, Elisa; Grassi, Eleonora; Grego, Mateja; Balsamo, Maria; Basili, Marco; Semprucci, Federica
Abstract: Free-living nematodes were investigated in three Mediterranean commercial ports (Ancona and Trieste, Italy; Koper, Slovenia) in terms of abundance, diversity and functionality. Results indicated that r-strategist genera were dominant in all ports and that a more diverse assemblage characterized Trieste, despite the high contamination levels, suggesting a potential adaptation to long-standing contamination. The main environmental factor that shaped the assemblage in all ports were Total Polycyclic Aromatic Hydrocarbons, while Total Organic Carbon and the grain-size were less relevant. A co-occurrence analysis was applied for identifying which genera cohesively respond to site-specific environmental conditions in order to recalibrate and implement the sets of bioindicator genera in relation to their different opportunistic behaviour. Finally, we provided some suggestions for a proper application of the nematode indices (Maturity Index, Index of Trophic Diversity, Shannon diversity) in order to encourage the use of free-living nematodes for the environmental quality assessment of commercial ports. Highlights: Nematodes can adapt to long standing contamination. The co-occurrence analysis can identify site-specific nematodes. New sets of sensitive/tolerant nematode genera are suggested for ports. EQS assessment in ports require the use of MI together with other metrics (e.g. H′ and c-p%).